Influencia del bullying en el desempeño académico de los estudiantes con discapacidad física de Educación General Básica - Arteaga Sornoza, Kelvin Stalyn (2023)
The present degree work Influence of bullying on the academic performance of students with physical disabilities in basic general education, which was carried out in the Bartolomé Garelli High School, is based on the cases of bullying that have occurred in the mentioned place, many manifestations of bullying are directed to students with disabilities. Various manifestations are directed to students with physical disabilities, this leads to emotional and psychological effects and to psychological and emotional effects, and in turn causes a decrease in academic performance. In order to carry out the study, a mixed approach methodology was used, that is to say, qualitative and quantitative, with a descriptive scope, which allows us to obtain a clear perception of the problem and a clear perception of the problem, obtaining the characteristics, causes and consequences of bullying. The techniques used for data collection were several interviews directed to the DECE and the Principal; and the survey directed to teachers and students............